Outcomes and Toxicities of Programmed Death‐1 (PD‐1) Inhibitors in Hodgkin Lymphoma Patients in the United States: A Real‐World, Multicenter Retrospective Analysis. (19th December 2018) - Bair, Steven M.; Strelec, Lauren E.; Feldman, Tatyana A.; Ahmed, Gulrayz; Armand, Philippe; Shah, Nirav N.; Singavi, Arun N.; Reddy, Nishitha; Khan, Nadia; Andreadis, Charalambos; Vu, Khoan; Huntington, Scott F.; et al.
Abstract: Background: Although classical Hodgkin lymphoma (cHL) is highly curable, 20%–30% of patients will not be cured with conventional treatments. The programmed death‐1 (PD‐1) inhibitors (PD‐1i) nivolumab and pembrolizumab have been Food and Drug Administration‐approved for relapsed/refractory (R/R) cHL. There is limited data on the real‐world experience with PD‐1i in cHL and it is unknown whether fewer selected patients treated with PD‐1i derive benefits similar to those observed in published trials. Materials and Methods: We performed a multicenter, retrospective analysis of R/R cHL patients treated with PD‐1i in the nontrial setting. The primary objective was to describe progression‐free survival (PFS) and overall survival (OS) in this population. Secondary objectives were to characterize response rates, toxicities, discontinuation patterns, and post‐PD‐1i therapies. Results: The study included 53 patients from nine U.S. centers. Overall response rate (ORR), complete response (CR), and partial response (PR) to PD‐1i were 68%, 45%, and 23%, respectively. Twelve‐month OS and PFS were 89% and 75%, respectively; median PFS was 29 months. Ninety‐six percent of patients with CR continue to respond at a median follow‐up of 20 months. Toxicities were similar to those previously described. Seventy percent of patients treated with systemic therapy after PD‐1i demonstrated objective responses. Conclusion: To our knowledge, this analysis is the first describing real‐world experience with PD‐1i in cHL patients in the U.S. Here, we demonstrate similar response rates compared to prior studies. The toxicity profile of PD‐1i was similar to that seen in previous studies; we further describe toxicity patterns in those with prior autoimmune disease or allogeneic transplant. Post‐PD‐1i systemic therapies appear active. These results support the effectiveness and tolerability of PD‐1i therapy in R/R cHL in a real‐world setting. Abstract : Until now, no studies have evaluated the effectiveness of PD‐1 inhibitors in classical Hodgkin lymphoma in a real‐world context (outside the context of study protocols). This article reports on clinical response to PD‐1 inhibitors, progression‐free and overall survival, and the prevalence and management of immune‐related adverse events in a population of patients with relapsed or refractory Hodgkin lymphoma treated with PD‐1 inhibitors.